The Effect of COVID-19 on Land Transport Within the European Union and Guidelines for its Stable Development - Tzvetkova, Svetla (European Journal of Sustainable Development, 2021)
The COVID-19 pandemic delivered a devastating blow to land transport in Europe. The measures adopted for its containment drastically reduced services provided by railway transport and motor transport. Despite the limited demand during the pandemic, transport carriers did not cease their activities and proved their place in Europe’s logistics chain. In order to overcome the negative effects of the crisis and restore mobility within the EU, transport firms require financial help and support. The present article reveals the negative results of the activity of passenger and cargo carriers within the EU in 2020 and makes inferences and recommendations for overcoming the negative situation faster on the basis of data presented by Eurostat about the impact that the COVID-19 pandemic has had on land transport. The presented data from Eurostat on the impact of the COVID-19 pandemic has served as a basis to make the respective inferences and indicate the fundamental guidelines for the stable development of land transport within the EU. Since railway transport is the safest, most secure and environmentally friendly type of transport, the focus is on the necessity for priority support of its activities.